Transfusion-associated adverse events and implementation of blood safety measures - findings from the 2017 National Blood Collection and Utilization Survey - Savinkina, Alexandra A. (Transfusion, 2020)
BACKGROUND: Serious transfusion-associated adverse events are rare in the United States. To enhance blood safety, various measures have been developed. With use of data from the 2017 National Blood Collection and Utilization Survey (NBCUS), we describe the rate of transfusion-associated adverse events and the implementation of specific blood safety measures. STUDY DESIGN AND METHODS: Data from the 2017 NBCUS were used with comparison to already published estimates from 2015. Survey weighting and imputation were used to obtain national estimates of transfusion-associated adverse events, and the number of units treated with pathogen reduction technology (PRT), screened for Babesia, and leukoreduced. RESULTS: The rate of transfusion-associated adverse events requiring any diagnostic or therapeutic interventions was stable (275 reactions per 100,000 transfusions in 2015 and 282 reactions per 100,000 transfusions in 2017). In 2017 among US blood collection centers, 16 of 141 (11.3%) reported screening units for Babesia and 28 of 144 (19.4%) reported PRT implementation; 138 of 2279 (6.1%) hospitals reported transfusing PRT-treated platelets. In 2017, 134 of 2336 (5.7%) hospitals reported performing secondary bacterial testing of platelets (50,922 culture-based and 63,220 rapid immunoassay tests); in 2015, 71 of 1877 (3.8%) hospitals performed secondary testing (87,155 culture-based and 21,779 rapid immunoassay tests). Nearly all whole blood/red blood cell units and platelet units were leukoreduced. CONCLUSIONS: Besides leukoreduction, implementation of most blood safety measures reported in this study remains low. Nationally, hospitals might be shifting from culture-based secondary bacterial testing to rapid immunoassays.